Global observations of cloud‐sensitive aerosol loadings in low‐level marine clouds. Issue 21 (5th November 2016) - Andersen, H.; Cermak, J.; Fuchs, J.; Schwarz, K.
Abstract: Aerosol‐cloud interaction is a key component of the Earth's radiative budget and hydrological cycle, but many facets of its mechanisms are not yet fully understood. In this study, global satellite‐derived aerosol and cloud products are used to identify at what aerosol loading cloud droplet size shows the greatest sensitivity to changes in aerosol loading ( A C S max ). While, on average, cloud droplet size is most sensitive at relatively low aerosol loadings, distinct spatial and temporal patterns exist. Possible determinants for these are identified with reanalysis data. The magnitude of A C S max is found to be constrained by the total columnar water vapor. Seasonal patterns of water vapor are reflected in the seasonal patterns of A C S max . Also, situations with enhanced turbulent mixing are connected to higher A C S max, possibly due to intensified aerosol activation. Of the analyzed aerosol species, dust seems to impact A C S max the most, as dust particles increase the retrieved aerosol loading without substantially increasing the concentration of cloud condensation nuclei. Key Points: The sensitivity of cloud properties to changes in aerosol loading changes with the magnitude of the aerosol loading Generally, the sensitivity is highest at comparatively low loadings, with regional and seasonal differences Environmental conditions, in particular, humidity, lead to marked shifts in the most effective aerosol loading